CAD/CAM applications: status and impact in Nigerian industrial sector (2010)
This research assessed, among others, the current status and the impact of Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) applications in the Nigerian industrial and technological sector. Two prominent cities Lagos and Ibadan were selected as centers of case studies to establish the level of the applications. Data was collected from industries within the 2 cities in the areas of manufacturing, design, production, construction and consultancy service units during a yearlong study. From the survey, 56% of companies visited in Lagos metropolis apply Computer-Aided Engineering (CAE) activities in their operations. Also 60% of the companies considered in Ibadan metropolis apply CAE, of which 75% are into CAD, 12.5% are applying CAM whereas 12.5% are utilizing Computer Numerically Controlled (CNC) machines. Conclusively, the commonest CAD techniques employed by the industries surveyed are Auto CAD and Archi CAD representing 55.6% and 33.3% of the total packages being used in the visited companies respectively.